Biskuit CERIA (Cangkang Telur Kombinasi Kurma dan Madu) sebagai Snack Alternatif untuk Meningkatkan Status Gizi Anak - Hema Dewi Anggraheny; Aisyah Lahdji; Tri Kartika Setyarini; Ika Dyah Kurniati (Universitas Muhammadiyah Semarang, 2023)
Many studies state that most cases of malnourished children, such as stunting, experience a lack of calories and protein. So that one of the focuses is to improve the nutritional status of children, especially by making food preparations from ingredients that are high in calories and protein, and of course those that are of interest to children in terms of taste and shape. Egg shells are an alternative food ingredient that is rich in protein and calcium. In addition, dates and honey produce a natural sweet taste, and have high nutritional value. The purpose of this activity is to provide alternative snacks for children in the form of eggshell cookies, a combination of dates and honey. The method starting with making egg shell cookies a combination of dates and honey (Ceria), and determining the right recipe for these biscuits, in terms of taste and shape. Then tested the nutritional composition (calories, carbohydrates, protein, fat, sugar, and fiber). Furthermore, the cookies were distributed to partners, namely mothers who have children aged 6 months to 9 years and health cadres in the Kedungmundu Village, Semarang. The result for this research was Ceookies “Ceria” with the ingredients of eggshell flour, wheat flour, cornstarch, dates, honey, and egg yolks. The nutritional composition produced in 100 grams of cookies produces 511 kcal calories, 63,7 grams of carbohydrates, 0,83 grams of protein, 28,3 grams of fat, 49,5 grams of fiber, and 7 grams of sugar. Ceria cookies (egg shell combination of dates and honey) can be given as an alternative food supplement for children, with the appropriate nutritional composition and using natural ingredients without artificial sweeteners or preservatives.